O-44 Return to the sport of soccer players after arthroscopic treatment consequences of ankle injury. (18th November 2016) - Starzyk, Maciej; Kentel, Maciej; Czamara, Andrzej; Królikowska, Aleksandra
Abstract : Purpose: The aim of this study was to the outcome evaluation of the arthroscopic treatment the ankle injuries in the group of soccer players as well as an assessment of returning time to football pitch. Materials and methods: This is a retrospective study including all soccer players aged <44 years who underwent arthroscopic treatment of ankle injury between 2007 and 2014 (m, 34; f, 10; mean age 24, 2 ± 6.1 years; follow-up 49.6 ± 6.6 months). Every patients playing in the 1st Division, European league, and 2nd Division. Indications to arthroscopy was chronic ankle pain, arthrofibrosis, anterior ankle impingement, intraarticular contractures and loose bodies, post- traumatic osteochondral lesions, osteochondritis dissecans, ankle instability. Surgical procedure- anteromedial and lateral portals were made by stab incisions. Numerous procedure are performed during arthroscopy of the ankle joint: loose bodies, osteophyte resection, cheilotomy, drilling, release of the joint contracture, debridement of ATFL lesion borders, capsular shrinkage, microfractures of the post-traumatic osteochondral lesions. Postoperatively, compression bandage was applied for 2 to 4 days. After the arthroscopy special rehabilitation protocol was immediately initiated. Level and delay of return to sport, clinical outcome according to the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Scale score, ROM, apprehension level and avoidance behaviour were noted. Results: The whole group of 34 males and 10 females returned to sport with average of 3.8 ± 1.4 months. 88, 7 % (39 patients) returned to the same level. Mean AOFAS score improved from 65/100 (52 -80) to 87/100 (54–100) (p < 0.05) Mean dorsiflexion improved from 7 degrees to 16 degrees (p < 0.009) and mean plantar flexion from 20 degrees to 34 degrees (p < 0.004). The fair and poor results were associated with severe ankle sprain leading to ligaments ruptures or fractures where several chondral lesions were to be found with arthroscopy At 49 months 44 patients rated the results of the operations as good 26 (59%) and excellent 11 (25%), 6 (13%) as fair and 1 as poor. 33 patients were subjectively satisfied of the surgery. Median preoperative duration of symptoms was 3 years. Most importantly, no significant complications were encountered. Complications included three patients with temporary numbness in the scar region and one patient with temporary ankle stiffness. Conclusions: Most football players resumed their main sport often at the same level. Medium return to the football pitch time of high level soccer players is related or the severity of injury and varies from to 3 to 4 months (3.8 ± 1.4 months). Arthroscopy treatment of the ankle sprain is safe and noteworthy method of treatment, which helps the ability of quick return to the sport.